Ants, Spiders or Bees... or Ticks? A Typology of Old Testament Scholarship in South Africa since 1994 within its African Context - Hendrik Ludolph Bosman (Old Testament Essays, 2015)
Looking back over the past two decades of Old Testament scholarship in South Africa, trends emerge that to some extent resemble the taxonomy of scientific endeavour made by Francis Bacon in 1620: • Like ants, some of us prefer to collect philological data to engage with biblical texts primarily on a literary and synchronic level. • Others are like spiders who on a diachronic level produce (“spin”?) new hypotheses about the (re)construction of elements of ancient Israel’s past as history. • There are also the odd few bees who try to relate and even integrate synchronic and diachronic interpretations of biblical texts that will result in producing “theological-ethical honey” as nourishment for  faith communities (especially in different African contexts). Bees can be found in widely diverging scholarly contexts: ie. “theological-ethical honey” can manifest itself in different modes such as African, Black and Feminist theologies.